Early migration patterns of calcium phosphate versus hydroxyapatite-coated stem in uncemented total hip arthroplasty: a prospective randomized clinical trial using radiostereometric analysis - Emelie S. Kristoffersson; Daniel Wästerlund; Anette Nyberg; Sead Crnalic; Kjell G. Nilsson; Volker Otten (Arthroplasty)
Abstract Background and purpose The design and coating of uncemented joint implants impact bone ingrowth and thereby the stability of the implant. This prospective randomized clinical trial aimed to compare early migration of two uncemented, similarly shaped femoral stems with either calcium phosphate or hydroxyapatite coating. Patients and methods 93 patients (102 hips) were randomized to either an intervention calcium phosphate or a conventional hydroxyapatite-coated stem. Migration measurements were performed postoperatively, and at 6 weeks, 3, 12 months, and 2 and 5 years after operation, and analyzed with radiostereometric analysis. Results There were no significant differences in migration between the two stems from postoperative to 5-year follow-up. With 6 weeks follow-up as baseline, the calcium phosphate coated stem showed a tendency towards migrating less with a maximum total point motion up to 2 years of 0.84 mm (0.68 to 1.00 95% CI) compared to the hydroxyapatite-coated stem which migrated 1.25 mm (0.99 to 1.52 95% CI) (P = 0.010). Conclusions Our data show that the calcium phosphate-coated stem is a safe implant in terms of ingrowth stability, and with migration patterns comparable to a hydroxyapatite-coated stem.